2022
DOI: 10.3390/app122412908
|View full text |Cite
|
Sign up to set email alerts
|

Computational Biology and Machine Learning Approaches Identify Rubber Tree (Hevea brasiliensis Muell. Arg.) Genome Encoded MicroRNAs Targeting Rubber Tree Virus 1

Abstract: Tapping panel dryness (TPD), a complex physiological syndrome associated with the rubber tree (Hevea brasiliensis Muell. Arg.), causes cessation of latex drainage upon tapping and thus threatens rubber production. Rubber tree virus 1 (RTV1) is a novel positive-sense single-stranded RNA virus from the Betaflexiviridae (genus Capillovirus), which has been established to cause TPD. MicroRNAs (miRNAs) play an important role in the interplay between viruses and host cells. In this study, we identified the rubber tr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…In our previous studies, we have investigated experimentally validated mature locus-derived microRNAs in the sugarcane genome, which were predicted to be targets of SCBGAV, SCYLV, and SCBV based on in silico criteria [37][38][39]. Several studies have identified complex host-virus interactions and have investigated miRNAs targeting plant viruses using an in silico approach [86][87][88][89][90][91][92]. miRNAs have emerged as novel endogenous targets for multiple levels of miRNA gene-level regulation [53,93,94].…”
Section: Discussionmentioning
confidence: 99%
“…In our previous studies, we have investigated experimentally validated mature locus-derived microRNAs in the sugarcane genome, which were predicted to be targets of SCBGAV, SCYLV, and SCBV based on in silico criteria [37][38][39]. Several studies have identified complex host-virus interactions and have investigated miRNAs targeting plant viruses using an in silico approach [86][87][88][89][90][91][92]. miRNAs have emerged as novel endogenous targets for multiple levels of miRNA gene-level regulation [53,93,94].…”
Section: Discussionmentioning
confidence: 99%
“…The ICMV-Ker is a bipartite begomovirus that spread to India and nearby locales in Southeast Asia during the past two decades. Several studies have investigated potential endogenous host-plant mature microRNAs that may target plant viruses based on in silico criteria [ 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 ]. The miRNAs have evolved as key endogenous biomolecules for regulating gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous studies, we have investigated experimentally validated sugarcane genome-encoded mature microRNAs that were predicted to target SCBGAV, SCYLV and SCBV based on in silico criteria [37][38][39]. Several studies have identified complex host-virus interactions and have investigated host-plant miRNAs targeting plant viruses using an in silico approach [97][98][99][100][101][102][103]. The miRNAs have evolved as novel endogenous targets for multiple layers of miRNA-gene level regulation [52,104,105].…”
Section: Discussionmentioning
confidence: 99%